Evaluating electrical stability in left bundle branch area pacing for bradycardia patients at follow-up - Sem Briongos-Figuero, MD, PhD; Álvaro Estévez Paniagua, MD, PhD; Manuel Tapia Martínez, MD; Silvia Jiménez Loeches, MD; Ana Sánchez Hernández, MD; Delia Heredero Palomo, RN; Elena Sánchez López, RN; Arantxa Luna Cabadas, RN; Roberto Muñoz-Aguilera, MD, PhD (Heart Rhythm O2)
Background: Physiologic pacing is safe and feasible, but whether electrical synchrony persists at follow-up in patients undergoing left bundle branch area pacing (LBBAP) is unknown. Objective: To determine performance of electrical synchrony in LBBAP patients at follow-up. Methods: Consecutive patients with successful LBBAP for bradycardia pacing indication and preserved left ventricular ejection fraction were selected. At follow-up, a 12-lead electrocardiogram (ECG) was recorded along with echocardiography for myocardial work analysis. V6-R wave peak time (RWPT), V1-RWTP, and QRS duration were compared. Results: One hundred forty-nine patients were studied. After 18.2 ± 7.3 months, V6-RWTP decreased from 74.4 ± 8.9 milliseconds to 71.5 ± 10.6 milliseconds (P < .001) in LBBP captures and from 90.9 ± 7.2 to 85.7 ± 9.3 milliseconds (P = .011) in left ventricular septal pacing (LVSP) captures. V1-RWPT decreased from 120.5 ± 13.1 to 111.7 ± 11.8 milliseconds at follow-up (P < .001) in LBBP and from 118.6 ± 9.9 to 115.2 ± 12.1 milliseconds (P = .052) in LVSP. Paced QRS duration was also significantly reduced in LBBP (from 115.3 ± 13.6 to 107.6 ± 12.8 milliseconds at follow-up; P < .001). At follow-up, 29 patients lost the right bundle branch (RBB) delay pattern in lead V1, but QRS duration remained unchanged (111.3 ± 10.7 at implant vs 109.6 ± 12.5 milliseconds at follow-up; P = .413), as did V6-RWPT, in both LBBP (73.4 ± 5.9 at implant vs 73.1 ± 6.9 milliseconds at follow-up; P = .860) and LVSP captures (86.3 ± 5.6 at implant vs 85.3 ± 8.1 milliseconds at follow-up; P = .658). Mechanical synchrony in patients with and without RBB delay pattern was similar. Conclusions: In patients undergoing LBBAP for bradycardia pacing, electrical synchrony remained stable over time, suggesting that LBBAP is a reliable and durable method for physiologic pacing.